Effects of wheat flour supplemented with soy protein concentrate on the rheology, microstructure and water mobility of protein‐fortified precooked noodles. (4th April 2022) - Yoon, Seong; Yang, Geunhyuk; Kwon, Hyukjin; Lee, Suyong
Summary: Wheat flour was supplemented with different levels of soy protein concentrate (SPC) and applied to precooked noodles for protein fortification whose quality attributes were characterised in terms of rheology, microstructure and water mobility. The wheat flours with high levels of SPC showed lower enthalpy values and higher temperatures derived from starch gelatinisation. They also exhibited lower values of the pasting viscosity and dynamic viscoelastic parameters. The mixolab measurements demonstrated that the supplement with SPC was effective in raising the water absorption and dough stability of wheat flour. In addition, the use of SPC‐supplemented wheat flours produced precooked noodles with tight and dense structures, which were confirmed by scanning electron microscopic analysis. These microstructural changes were consequently related to higher maximum resistance to extension and lower extensibility of the noodles. However, the SPC‐supplemented wheat flours did not significantly affect the cooking loss of the noodles. Furthermore, three water components with different mobility were observed in the precooked noodles whose spin‐spin relaxation times were distinctly reduced with increasing levels of SPC. Overall similarities in the sensory noodle attributes were detected as wheat flour was supplemented with SPC at a level of 8% (w/w). Abstract : Precooked noodles were fortified with protein by the use of wheat flour supplemented with soy protein concentrate (SPC).